Exploring the relationship between preeclampsia and human epididymis protein 4: Preeclampsia and human epididymis protein 4 - Cimilli Senocak, Gamze Nur; Borekci, Bunyamin; Halici, Zekai; Topdagi Yilmaz, Emsal Pinar (Journal of Surgery and Medicine, 2022)
Background/Aim: The level of human epididymis protein 4 (HE4), a glycoprotein and protease inhibitor, increases under many malignancies and inflammatory conditions. HE4 is also associated with cell invasion, migration, and adhesion. In this study, we compared the HE4 protein levels in pregnant patients with preeclampsia to healthy pregnant and non-pregnant individuals with the aim of finding a biomarker that can be used to recognize preeclampsia. Methods: Our study is a prospective case control study and included 20 pregnant women with preeclampsia, 20 pregnant women without preeclampsia, and 20 healthy non-pregnant women (the control). The participants’ serum HE4 levels were analyzed statistically. Results: Data analysis revealed that the mean HE4 levels were significantly lower in the preeclampsia group than in the other two groups (P = 0.002). Mean HE4 protein levels were also lower in the non-pregnant women than in the pregnant women without preeclampsia; however, this difference was not significant. Conclusion: It is difficult to predict preeclampsia, and there is not any sensitive or specific biomarker for determining the condition. This study may support that HE4 protein may be useful and significant in predicting preeclampsia. The results we achieved provide proof that HE4 levels could be a potential biomarker for preeclampsia. Many more comprehensive studies are needed to support the association between HE4 protein and preeclampsia.